2019
DOI: 10.3390/polym11020194
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Study of Zinc Orotate and Its Synergistic Effect with Commercial Stabilizers for Stabilizing Poly(Vinyl Chloride)

Abstract: Zinc orotate (ZnOr2), which is a new kind of poly(vinyl chloride) (PVC) stabilizer, is prepared in this work through the precipitation method, and its impact on the thermal stability of PVC is measured by thermogravimetric analysis (TG), Congo red test, and discoloration test. The results exhibit that the thermal stability of PVC is positively enhanced after the addition of ZnOr2. In contrast with a commercial thermal stabilizer, zinc stearate (ZnSt2), a noteworthy improvement was observed that ZnOr2 could pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Metal soap, such as calcium stearate (CaSt2), and zinc stearate (ZnSt2), has no toxicity, but the thermal stabilizing effect on PVC is not ideal, especially the "zinc-burning" will lead to rapid degradation of PVC [5][6][7][8][9][10] . Organotin has an excellent thermal stability on PVC, but the cost of is too high [11] . It is then necessary to develop new non-toxic and efficient thermal stabilizer of PVC [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal soap, such as calcium stearate (CaSt2), and zinc stearate (ZnSt2), has no toxicity, but the thermal stabilizing effect on PVC is not ideal, especially the "zinc-burning" will lead to rapid degradation of PVC [5][6][7][8][9][10] . Organotin has an excellent thermal stability on PVC, but the cost of is too high [11] . It is then necessary to develop new non-toxic and efficient thermal stabilizer of PVC [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…A number of new types of thermal stabilizers, for example, zinc and calcium salts of 11-maleimideoundecanoic acid, liquid Ca/Zn thermal stabilizer synthesized, zinc and calcium oxolinic complexes, ricinoleic acid-based Ca/Zn stabilizer, have been reported [11,13,[15][16][17][18][19] . Some researchers also indicated that polyols can serve as auxiliary thermal stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…6, It can be observed that the stretching vibration peak and symmetric stretching vibration peak of COOH group for K(H 2 Or) were transferred from 3468.64 and 1378.10 to 3436.56 and 1384.60 cm −1 , respectively, after formation of Zn complex. In Zn-orotate complex a peak at 1637.78 cm −1 corresponding to (-NH-CO-) group [40]. At room temperature, Fig.…”
Section: Ftir Pxrd and Thermogravimetric Analysismentioning
confidence: 92%
“…We can be noticed from figure 8 which represents the congo-red test for plasticized poly(vinyl chloride) containing Oxydtron that the time required for beginning and ending of the color change process measured by this test is short; because the thermal stability of poly(vinyl chloride) is low [41,42]. But after adding Oxydtron the stability of poly(vinyl chloride) has been improved, where this behavior is the outcome of the synergistic action of Oxydtron with Newstab stabilizer which is calcium-zinc based stabilizer as mentioned and this synergistic action will increase the stability of poly(vinyl chloride) against discoloration and reduced the chlorine release.…”
Section: Congo-red Testmentioning
confidence: 99%